Design and Prototyping of a Mechanical Pedaling System for Separating and Sieving Sand. - Ahimbisibwe, Peter Marvin (Kabale University, 2023)
Sand is a valuable non-renewable commodity used for building in this rapidly growing global construction market. It is one of the highest volumes of raw materials used after water. Due to several advancements in techniques of construction, the quality of sand has also been critically considered. For example; plastering or wall finishes would require fine smooth sand particles most preferably river sand. This has led to processes like sieving where sand particles are separated according to particle sizes. Various sieving methods have been invented and innovated such as rotary and vibratory sieving machines which are electrically powered. However, the widespread use of these innovations is still low due to the high daily electricity expenses, high purchase prices, and low incomes of users. Therefore, majority of the builders and small-scale construction sites still rely on the hand-operated manual sieving method. It is due to this that I designed a mechanical pedal powered sand sieve machine. It is targeted to solve the problem of affordability of an efficient sieving machine. The machine uses a mechanical crank slider pedaling system which makes it more affordable. The machine will impact the lives of the user because affordable, time-saving, less human effort during operation, and flexible. This project therefore focused on designing and constructing this mechanical pedal powered sand sieving machine. Several analytical and numerical analyses and design procedures were followed to implement this.